2015
DOI: 10.1186/s12871-015-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

The utility of initial procalcitonin and procalcitonin clearance for prediction of bacterial infection and outcome in critically ill patients with autoimmune diseases: a prospective observational study

Abstract: BackgroundThe diagnostic value of procalcitonin (PCT) for patients with autoimmune diseases (AID) remains controversial and few studies focused on ICU patients. We sought to determine its diagnostic and prognostic values in this clowd.MethodsA prospective observational study was conducted in AID patients admitted to the ICU. Serum PCT levels were measured on ICU admission and subsequently at days 1, 3, 5 and 7, and peak PCT levels within 24 h (PCTpeak) were analyzed the utility for bacterial infection. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Shi et al reported that SOFA scores of a non-survivor group were significantly higher than those of a survivor group (8.9±2.1 versus 5.4±2.2) [ 14 ]). In another recent study by Kim et al, the mean SOFA score of the non-survivor group was reported as 5 (range, 3–8) which was significantly higher than that of the survivor group [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al reported that SOFA scores of a non-survivor group were significantly higher than those of a survivor group (8.9±2.1 versus 5.4±2.2) [ 14 ]). In another recent study by Kim et al, the mean SOFA score of the non-survivor group was reported as 5 (range, 3–8) which was significantly higher than that of the survivor group [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SOFA score 14 is a scoring system used to determine sepsis-related organ dysfunction based on assessed levels of respiratory, cardiovascular, coagulation, renal, and nervous system dysfunction in patients. Shi et al 15 reported that the SOFA score of the non-survivor group was significantly higher than that of the survivor group (8.9 ± 2.1 vs 5.4 ± 2.2). In another recent study by Kim et al, 4 a mean SOFA score of 5 was found in the non-survivor group was 5, which was significantly higher than that in the survivor group.…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy of serial PCT concentrations has been evaluated as a prognostic biomarker of outcome in sepsis [28,29]. PCT clearance has also been extensively studied as a biomarker for monitoring sepsis outcomes; at this end various reports have demonstrated significant improvement in PCT clearance in survivors compared to nonsurvivors in both severe sepsis and septic shock patients [28,[30][31][32]. A large meta-analysis comprising 23 studies with 3944 patients concluded that PCT nonclearance was a prognostic factor of death in patients with sepsis [33].…”
Section: Procalcitonin (Pct)mentioning
confidence: 99%